2018
DOI: 10.1111/prd.12236
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral models for periodontal health and disease

Abstract: The oral health-related behavior of patients with periodontal disease is a critical determinant of their health. Psychological models of behavior provide a framework for the design of interventions to enhance oral health-related behavior. This article reviews published manuscripts on interventions to enhance oral health-related behavior, classifying the nature of the interventions according to current psychological models of behavior. Fifteen manuscripts reporting the findings of 14 studies were identified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…49 Both investigations based on visual-aided approach yielded better outcomes than conventional oral hygiene instructions, 23,29 probably due to patients' more vivid perception of biofilm composition and its effects on oral health. This is in line with what was advocated by Newton et al 21 : the motivational and capability areas are vividly stimulated when young individuals are called to look at images showing the consequences of their own poor oral hygiene habits.…”
Section: Repeated Oral Hygiene Instructions and Visual-aided Approachsupporting
confidence: 88%
“…49 Both investigations based on visual-aided approach yielded better outcomes than conventional oral hygiene instructions, 23,29 probably due to patients' more vivid perception of biofilm composition and its effects on oral health. This is in line with what was advocated by Newton et al 21 : the motivational and capability areas are vividly stimulated when young individuals are called to look at images showing the consequences of their own poor oral hygiene habits.…”
Section: Repeated Oral Hygiene Instructions and Visual-aided Approachsupporting
confidence: 88%
“…Interventions for planning have been adopted in healthcare studies [30,32] and are regarded as an effective approach to enable people to translate their “good” intentions into action. Furthermore, interventions incorporating elements of goal setting, planning the behavior, and monitoring the behavior (GPS elements) were reported to be effective in creating behavior change [46]. To put motivation into action, we integrated GPS elements into the intervention design to create opportunities for patients to implement oral self-care, including setting goals to brush the teeth at least twice a day, planning for possible times to perform oral cleaning through setting a reminder, and self-monitoring to brush the teeth in a sequential order lasting up to 3 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that interventions to enhance adherence to periodontal infection control are often complex and contain several behavioral change techniques. The most common techniques identified were “shaping knowledge,” “goals and planning,” and “feedback and monitoring.” The interventions that used goals and planning and feedback and monitoring were considered the most effective in supporting the patients to change behavior …”
Section: Psychological Consideration Of Health Behavior Changementioning
confidence: 99%
“…A systematic review by Newton and Asimakopoulou focused on the identification of behavioral change techniques used in interventions to enhance patients’ motivations for effective periodontal infection control. Only randomized controlled studies with patients aged 18 years or over and diagnosed with periodontal disease were included.…”
Section: Psychological Consideration Of Health Behavior Changementioning
confidence: 99%